Pengaruh Kompetensi, Profesionalisme, Dan Pengalaman Kerja Auditor Terhadap Kualitas Audit Internal Pada Perusahaan Swasta Dan Bumn Di Padang - Ragil Gusfiardi1; Charoline Cheisvyanny; Vita Fitria Sari (Universitas Negeri Padang, 2019)
This study aims to determine the effect of Influence of competence, professionalism, and work experience on the quality of internal audit in private and state-owned companies in the city of Padang. The population in this study are private companies and state-owned companies in the city of Padang, which have several internal auditors in their company. The sample in this study were all internal auditors in private companies and BUMN in the city of Padang. Data source is primary data. Data collection techniques with a questionnaire. The data analysis technique is multiple linear regression. The results showed that: (1) Competence had no significant effect on the quality of internal audit, where the tcount of 1.514 < 2, 042 ttable at sig 0.140> α 0.05 which meant H1 was rejected, (2) Professionalism had no significant effect on the quality of internal audit, where the value tcount 1,300 < 2,042 ttable at sig 0,204> α 0,05 which means H2 is rejected, and (3) Work Experience has a significant positive effect on the quality of internal audit, where tcount 2,704 > 2,042 ttable at sig 0,011 <α 0,05 which means H3 is accepted.